Flavonoid chemistry of Chuquiraga (Asteraceae) - Juárez, Berta Estela (2002)
Fresh plant material was collected in different Argentine provinces. A voucher of each specimen is deposited at the Herbarium of the Fundación Miguel Lillo (LIL). Chuquiraga atacamensis Kuntze collected in SALTA: Dept. Los Andes (LIL 603627); C. parviflora (Griseb.) Hieron. collected in CATAMARCA, Dept. Andalgalá (LIL 605897); C. straminea Sandwith collected in NEUQUEN, Dept. Collan-Cura (LIL 605812).